Interactions of polymeric drug carriers with DDT reduce their combined cytotoxicity. (October 2018) - Zhang, Xuejiao; Lei, Lei; Zhang, Haiyan; Zhang, Siyu; Xing, Weiwei; Wang, Jin; Li, Haibo; Zhao, Qing; Xing, Baoshan
Abstract: Attention has been paid to the environmental distribution and fate of nanomedicines. However, their effects on the toxicity of environmental pollutants are lack of knowledge. In this study, the negatively charged poly (ethylene glycol)- b -poly (L-lactide- co -glycolide) (mPEG-PLA) and positively charged polyethyleneimine-palmitate (PEI-PA) nanomicelles were synthesized and served as model drug carriers to study the interaction and combined toxicity with dichlorodiphenyltrichloroethane (DDT). DDT exerted limited effect on the biointerfacial behavior of mPEG-PLA nanomicelles, whereas it significantly mitigated the attachment of PEI-PA nanomicelles on the model cell membrane as monitored by quartz crystal microbalance with dissipation (QCM-D). The cytotoxicity of DDT towards NIH 3T3 cells was greatly decreased by either co-treatment or pre-treatment with the nanomicelles according to the results of real-time cell analysis (RTCA). The cell viability of NIH 3T3 exposed to DDT was increased up to 90% by the co-treatment with mPEG-PLA nanomicelles. Three possible reasons were proposed: (1) decreased amount of free DDT in the cell culture medium due to the partitioning of DDT into nanomicelles; (2) mitigated cellular uptake of nanomicelle-DDT complexes due to the complex agglomeration or electrostatic repulsion between complexes and cell membrane; (3) detoxification effect in the lysosome upon endocytosis of nanomicelle-DDT complexes. Graphical abstract: Highlights: Partitioning affinity of DDT to mPEG-PLA nanomicelles was higher than that to PEI-PA nanomicelles. DDT partitioning mitigated the interaction of positively charged nanomicelles with model cell membrane. Cytotoxicity of DDT was lowered by complexing with nanomicelles. Partitioning in nanomicelles decreased the available concentration, reduced the bioavailability, and altered the cellular uptake pathway of DDT.